2008
DOI: 10.1146/annurev.matsci.38.060407.130217
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Materials Sciences: Experimental Strategies for Accelerated Knowledge Discovery

Abstract: Combinatorial materials science offers an exciting experimental strategy for rapidly surveying a wide array of materials chemistries and process variables coupled to the screening of structure and properties. Adapting approaches used in synthetic organic chemistry for applications such as pharmaceutical sciences and chemical discovery, materials scientists have developed a variety of approaches to create libraries in the solid state in order to rapidly examine a broad range of materials characteristics; the ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
94
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(95 citation statements)
references
References 84 publications
0
94
0
1
Order By: Relevance
“…High-throughput, combinatorial experiments are a mainstay in several fields for rapid materials discovery, screening, evaluation and development [63][64][65][66][67]. These approaches rely on the production of materials libraries-a sample with controlled gradients that cover the material space of interest.…”
Section: High-throughput Experiments On Materials Libraries With Compmentioning
confidence: 99%
See 1 more Smart Citation
“…High-throughput, combinatorial experiments are a mainstay in several fields for rapid materials discovery, screening, evaluation and development [63][64][65][66][67]. These approaches rely on the production of materials libraries-a sample with controlled gradients that cover the material space of interest.…”
Section: High-throughput Experiments On Materials Libraries With Compmentioning
confidence: 99%
“…These approaches rely on the production of materials libraries-a sample with controlled gradients that cover the material space of interest. Materials libraries commonly use continuous or discrete composition gradients [64,66,67]. Libraries are usually made as thin films (typically < 1 m) using vapor techniques, but bulk methods such as diffusion multiples [67], additive manufacturing and 3D printing are becoming available.…”
Section: High-throughput Experiments On Materials Libraries With Compmentioning
confidence: 99%
“…It also adopts techniques from cheminformatics [63,64] and heavily relies on data mining [65,66]. Pioneering work on cheminformatics-type approaches and massive electronic structure calculations was, e.g., performed by Rajan et al [67][68][69] and Ceder et al [70], respectively, in the context of inorganic solids. An in silico study combining the scale and level of theory found in CEP is, however, unprecedented.…”
Section: The Harvard Clean Energy Projectmentioning
confidence: 99%
“…[1][2][3][4][5] Techniques for the synthesis of combinatorial libraries of materials include solution based methods, 6 advanced manufacturing, and physical vapor deposition. [7][8][9][10][11][12] Among these techniques, combinatorial sputtering provides an opportunity to carefully tune the properties of materials using various parameters such as source voltage, gas pressure, reactive gases, and deposition geometry, making this technique particularly amenable to synthesis of carefully designed, high-quality composition libraries.…”
Section: Introductionmentioning
confidence: 99%